Analisis Efektivitas Teknik File Carving pada Pemulihan Data Digital Menggunakan PhotoRec - Susanto; Irfan Hanafi; Narisa Aulia; Muhammad Jauhar Fardani; Muhammad Nur Irfan (Universitas Boyolali, 2026)
Data loss is a critical issue in the digital era, both in everyday computing and in forensic investigations. This study aims to evaluate the effectiveness of PhotoRec, an open-source file carving tool, in recovering lost files from a FAT32 storage medium. A strict digital forensic approach was applied by performing disk imaging, preserving evidence integrity, and documenting each stage in detail. Data loss was simulated through logical deletion and by scanning unallocated sectors to closely replicate real-case conditions. PhotoRec was then utilized to select the target media, identify partitions, determine the file system type, and scan free space to extract files based on signature recognition. The findings show that PhotoRec successfully recovered a total of 50 files, including all primary files deleted during the experiment. In addition, several system-related files such as ELF were also recovered, illustrating the aggressive nature of carving techniques that extract any recognizable data structure. These results confirm that PhotoRec can operate effectively in data loss scenarios on FAT32 media, even when file metadata is no longer available. This study contributes to a deeper understanding of PhotoRec’s performance within the context of digital forensics and highlights its relevance as an investigative tool that prioritizes accuracy, integrity, and procedural traceability.